Effect of pulmonary rehabilitation on peripheral muscle fiber remodeling in patients with COPD in GOLD stages II to IV. - Vogiatzis, Ioannis; Terzis, Gerasimos; Stratakos, Grigoris; Cherouveim, Evgenia; Athanasopoulos, Dimitris; Spetsioti, Stauroula; Nasis, Ioannis; Manta, Panagiota; Roussos, Charis; Zakynthinos, Spyros (Chest, 2011)
BACKGROUND: In most patients with COPD, rehabilitative exercise training partially reverses the morphologic and structural abnormalities of peripheral muscle fibers. However, whether the degree of improvement in muscle fiber morphology and typology with exercise training varies depending on disease severity remains unknown. METHODS: Forty-six clinically stable patients with COPD classified by GOLD (Global Initiative for Obstructive Lung Disease) as stage II (n = 14), III (n = 18), and IV (n = 14) completed a 10-week comprehensive pulmonary rehabilitation program consisting of high-intensity exercise three times weekly. RESULTS: At baseline, muscle fiber mean cross-sectional area and capillary density did not significantly differ between patients with COPD and healthy control subjects, whereas muscle fiber type I and II proportion was respectively lower (P < .001) and higher (P < .002) in patients with GOLD stage IV compared with healthy subjects and patients with GOLD stages II and III. Exercise training improved, to a comparable degree, functional capacity and the St. George Respiratory Questionnaire health-related quality of life score across all three GOLD stages. Vastus lateralis muscle fiber mean cross-sectional area was increased (P < .001) in all patient groups (stage II: from 4,507 ± 280 μm² to 5,091 ± 271 μm² [14% ± 3%]; stage III: from 3,753 ± 258 μm² to 4,212 ± 268 μm² [14% ± 3%]; stage IV: from 3,961 ± 266 μm² to 4,551 ± 262 μm² [17% ± 5%]), whereas all groups exhibited a comparable reduction (P < .001) in type IIb fiber proportion (stage II: by 6% ± 2%; stage III: by 6% ± 1%; stage IV: by 7% ± 1%) and an increase (P < .001) in capillary to fiber ratio (stage II: from 1.48 ± 0.10 to 1.81 ± 0.10 [23% ± 5%]; stage III: from 1.29 ± 0.06 to 1.56 ± 0.09 [21% ± 5%]; stage IV: from 1.43 ± 0.10 to 1.71 ± 0.13 [18 ± 3%]). The magnitude of changes in the aforementioned variables did not differ across GOLD stages. CONCLUSIONS: Functional capacity and morphologic and typologic adaptations to rehabilitation in peripheral muscle fibers were similar across GOLD stages II to IV. Pulmonary rehabilitation should be implemented in patients at all COPD stages.
Keywords: Exercise Therapy; Exercise Tolerance; Female; Humans; Male; Middle Aged; Muscle Fibers, Skeletal; Muscle Fibers, Slow-Twitch; Pulmonary Disease, Chronic Obstructive; Quality of Life; Recovery of Function; Treatment Outcome